Patient satisfaction as a pathway between service quality and loyalty: Insights from dental care services - Wasito, Wasito; Puspita, Euis Dara (Privietlab, 2026)
This study examines the effect of service quality on patient satisfaction and its implications for loyalty at Lapan Dental Care Clinic in Bandung Regency. A cross-sectional design with consecutive sampling was applied, involving 100 patients. Path analysis was employed to test the causal relationships among the variables. The findings reveal that service quality significantly influences patient satisfaction by 77.89%, with justice contributing the most (18.58%). Patient satisfaction significantly affects loyalty by 79.38% and mediates the relationship between service quality and loyalty, with a contribution of 87.88%. These results highlight the importance of improving service quality, particularly fairness and safety, to enhance patient satisfaction and foster loyalty. This study contributes empirical evidence to the literature on dental healthcare services in regions with limited facilities.